Oxygen radicals in biological systems. - Packer, Lester (Methods in enzymology ;, 1994)
Since biological tissues are unstable in an oxygen atmosphere, a great deal of effort is expended by organisms to metabolically limit or repair oxidative tissue damage. This volume of Methods in Enzymology and its companion Volume 234 present methods developed to investigate the roles of oxygen radicals and antioxidants in disease. Key Features * Generation, detection, and characterization of oxygen radicals, chemistry, biochemistry, and intermediate states of reductio* Isolation, characterization, and assay of enzymes or substrates involved in formation or removal of oxygen radical * Methods for assessing molecular, cell, and tissue damage; assays and repair of oxidative damage.